1995
DOI: 10.1159/000196475
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pneumonia due to <i>Legionella pneumophila</i> and <i>Mycoplasma pneumoniae</i> in a Population Admitted to a Department of Internal Medicine

Abstract: We studied 177 patients with pneumonia admitted to an internal medicine department over a period of 3 years to determine the incidence of two emerging pathogens, Legionellapneumophilaand Mycoplasma pneumoniae. Clinical, radiological and laboratory tests were performed and included blood cultures, serology, gram staining and sputum cultures. L.pneumophila was the agent involved in 9 patients (5.1%) and M. pneumoniae in 12 (6.8%). These prevalences were about in the middle of the range of previously published fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In evaluating the extent of atypical respiratory agents in our patients we found that specific sputum and BAL cultures for L. pneumophilia were positive in 5%, as were cultures for M. pneumoniae. Other studies give variable positivity rates for these organisms, ranging from 1% to 27 % [16,17]. Positive culture rates for these atypical pathogens more than likely depend on the patient population, socioeconomic factors, age, and possibility of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating the extent of atypical respiratory agents in our patients we found that specific sputum and BAL cultures for L. pneumophilia were positive in 5%, as were cultures for M. pneumoniae. Other studies give variable positivity rates for these organisms, ranging from 1% to 27 % [16,17]. Positive culture rates for these atypical pathogens more than likely depend on the patient population, socioeconomic factors, age, and possibility of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Legionella pneumophila, the causative agent of Legionnaires' disease, is recognized as a major cause of community and nosocomial epidemic pneumonia (8,13,26). The ability of L. pneumophila to cause disease is dependent on its ability to invade and replicate within human alveolar cells.…”
mentioning
confidence: 99%
“…Legionnaires' disease is a common pneumonia that occurs in both nosocomial and community settings (14,19,41). In the lungs of affected individuals, L. pneumophila replicates in phagocytic and possibly alveolar epithelial cells, within a specialized compartment that is surrounded by the host-cell rough endoplasmic reticulum (RER) and mitochondria (1,24,39,51,62).…”
mentioning
confidence: 99%